Analisis Kesalahan Berbahasa Indonesia pada Proposal Pengajuan PKM Unisda dengan Judul “Bcandy” Eksploitasi Banana Fruit Sebagai Teman Perjalnan yang Menyehatkan - Nur Aidatus Syarifah; Laila Tri Lestari; Anisa Ulfah (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to analyze Indonesian language errors contained in the proposal for the Student Creativity Program (PKM) of Uiversitas Islam Darul ‘Ulum (UNISDA) students with the title “BCandy” Exploitation of Banana Fruit as a Healthy Travel Companion. The focus of the research includes identifying types of language errors, such as errors in the use of punctuation marks and errors in the use of capital letters. The method used is descriptive qualitative with document analysis techniques to explore and describe errors systematically. The results show that there are still many language errors that occur, which are caused by students' lack of understanding of good and correct Indonesian language rules. These findings emphasize the importance of language coaching and training for students so that the quality of PKM proposal writing can improve and produce more professional scientific work.